Is Islamic banking stronger than conventional banking during the Covid-19 pandemic? Evidence from Indonesia - I Made Dauh Wijana; I Wayan Widnyana (Faculty of Economics, Universitas Islam Indonesia, 2022)
Purpose – We intended to test and compare the durability of Islamic banking and conventional banking during the Covid-19 pandemic in Indonesia. To that end, we first compared their performance before and during the pandemic. Next, we examined the effects of pandemic shocks on the performance of each of them.Methodology – The data covers 80 banks in Indonesia, which were divided into four groups, namely Islamic and conventional commercial banks, and Islamic and conventional rural banks. Each group consisted of 20 banks. Our observation period is 10 quarters, which was divided into two periods, namely the period before the pandemic (Q1-2019 – Q1-2020) and the period during the pandemic (Q2-2020 – Q2-2021). For comparison, we used a paired sample t-test, while testing the effect of shocks using a panel regression model.Findings – Islamic banking outperformed conventional banking, both before and during the Covid-19 pandemic. The Covid-19 pandemic has predominantly shaken conventional banking indicators and has only slightly shaken Islamic banking. However, this does not mean Islamic banks were superior to their conventional counterparts because both were shaken, it's just that conventional banks experienced a bigger shock than their Islamic counterparts.Originality – This is an original study that examines and compares the performance between Islamic and conventional banking using financial ratios during the Covid-19 pandemic.